PENGARUH WOOLWICH MASSAGE TERHADAP KELANCARAN PENGELUARAN ASI IBU POSTPARTUM DI RUMAH SAKIT WILAYAH KABUPATEN WONOSOBO - Sapti Widadi; Nazilla Nugraheni; Marwiati Marwiati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2023)
Breast milk is milk that contains all the nutrients a baby needs to grow and develop. WHO says that exclusive breastfeeding is very beneficial for mothers and babies, the most important thing is to protect babies from gastrointestinal infections so that the risk of infant death due to diarrhea and other infections. One of the efforts that can be made to increase lactation hormones is to do breast care. Stimulating oxytocin and prolactin in postpartum mothers is by creating a feeling of relaxation, one of which is by doing woolwich massage. Researchaims to determine whether or not there is an effect of woolwich massage on the smooth production of breast milk in portpartum mothers in hospitals in Kab. Wonosobo. The research method used was a quasy experiment with non-equivalent control group design. This study divided respondents into experimental groups and control groups. The population is the average postpartum vaginal mothers from January to May 2023 at RSI Wonosobo and RSUD KRT. Setjonegoro Wonosobo. The sampling techniques used were quota sampling and bivariate analysis with the Mann Whitney U test. The results showed there was a difference between the experimental group and the control group with a p-value of 0.013<α (0.05). Conclusion: asignificant effect of wooolwich massage on the smooth milk production of postpartum mothers.